Islamic equities : impact of the Islamic compliance review process on stock performance in Asia Pacific. - Mahathir Md. Satar. (2010)
Research Objectives: The main aim of this paper is to understand the principles underlying the Islamic Compliance Review Process (CRP) imposed on Islamic stocks and its impact on stock performance in the Islamic and conventional markets as a whole and within selected sectors, in different market conditions in Asia Pacific. Research Scope & Methodology: Firstly, using Jensen’s Alpha, Treynor’s Measure, Sharpe Ratio and the Market Efficiency Coefficient (MEC), the performances of Islamic and conventional indices were analyzed in market downtrend, uptrend and in the long-run. Secondly, to reduce sector-bias and effect of changing index composition, the performances of Islamic and conventional portfolios in the financial and industrial sectors were analyzed in the different market conditions. Lastly, the returns from the Asia Pacific market were regressed against that of the South East Asia and global markets, to investigate the applicability of the Asia Pacific results to smaller or broader markets. Research Findings (on the impact of CRP): Results show that (1) Islamic index outperformed the conventional index during market downtrend and in the long-run, but mixed results were obtained during market uptrend, (2) performance of indices and individual sectors differs implying that indices performance cannot be attributed to the size of the sector composition and (3) results in Asia Pacific region are not applicable to other regions implying that investment decisions cannot be based on results from the broader market but rather, on the specific regions in which to be invested in.